Evaluation of the effects of dapagliflozin, a sodium‐glucose co‐transporter‐2 inhibitor, on hepatic steatosis and fibrosis using transient elastography in patients with type 2 diabetes and non‐alcoholic fatty liver disease. Issue 2 (2nd October 2018) - Shimizu, Masanori; Suzuki, Kunihiro; Kato, Kanako; Jojima, Teruo; Iijima, Toshie; Murohisa, Toshimitsu; Iijima, Makoto; Takekawa, Hidehiro; Usui, Isao; Hiraishi, Hideyuki; Aso, Yoshimasa
Abstract : Aims: To investigate the effects of dapagliflozin on liver steatosis and fibrosis evaluated in patients with type 2 diabetes and non‐alcoholic fatty liver disease (NAFLD). Materials and methods: In a randomized, active‐controlled, open‐label trial, 57 patients with type 2 diabetes and NAFLD were randomized to a dapagliflozin group (5 mg/d; n = 33) or a control group (n = 24) and were treated for 24 weeks. Hepatic steatosis and fibrosis were assessed using transient elastography to measure controlled attenuation parameter (CAP) and liver stiffness, respectively. Results: Baseline liver stiffness measurement (LSM) was positively correlated with several markers and scoring systems for liver fibrosis. In week 24, there was a significant decrease in CAP from 314 ± 61 to 290 ± 73 dB/m ( P = 0.0424) in the dapagliflozin group, while there was no significant change in the control group. In addition, LSM tended to decrease from 9.49 ± 6.05 to 8.01 ± 5.78 kPa in the dapagliflozin group. In 14 patients from this group with LSM values ≥8.0 kPa, indicating significant liver fibrosis, LSM decreased significantly from 14.7 ± 5.7 to 11.0 ± 7.3 kPa ( P = 0.0158). Furthermore, serum alanine aminotransferase and γ‐glutamyltranspeptidase levels decreased in the dapagliflozin group, but not in the control group, and visceral fat mass was significantly reduced in the dapagliflozin group. Conclusions: Based on these findings, the sodium‐glucose co‐transporter‐2 inhibitor dapagliflozin improves liver steatosis in patients with type 2 diabetes and NAFLD, and attenuates liver fibrosis only in patients with significant liver fibrosis, although the possibility cannot be excluded that a reduction in body weight or visceral adipose tissue by dapagliflozin may be associated with a decrease of liver steatosis or fibrosis.